Smart Monitoring System For Hybrid Solar Power Plants Using Iot Technology - Agung Wirjawan; Andi Safarudin; Rika Ramdani; Ninik Sri Lestari; Givy Devira Ramadi; Sukirno Sukirno (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Solar Power Plants (PLTS) have become one of the most widely used sources of renewable energy across various sectors, including both commercial industries and households. A hybrid solar power system combines solar energy with other sources, such as generators or the electrical grid. The urgency of this research lies in the development of an Internet of Things (IoT)-based monitoring system for hybrid solar power plants, which can analyze data in real time, facilitate problem detection, optimize performance, and design preventive maintenance, as well as serve as an alternative source of electrical energy.The objective of this study is to develop a monitoring system for hybrid solar power plants using IoT. This technology is essential for enhancing the efficiency and sustainability of hybrid solar power generation. The method used in this research is the experimental method.Solar panels function as energy collectors that convert sunlight into electrical energy. The solar charge controller regulates the amount of electrical energy from the panels used to charge the battery. The voltage, current, and power generated by the plant are detected by two sensors: a DC voltage sensor and an ACS712 current sensor. The energy stored in the battery is used to power lamps. IoT offers an efficient solution for integrating components of a solar power plant, such as solar panels, inverters, batteries, and others. A hybrid solar power monitoring system can ensure maximum energy utilization and reduce long-term operational costs.